2011
DOI: 10.1002/cmdc.201000481
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Receptor Binding, and CNS Pharmacological Studies of New Thyrotropin‐Releasing Hormone (TRH) Analogues

Abstract: As part of our search for selective and CNS-active thyrotropin-releasing hormone (TRH) analogues, we synthesized a set of 44 new analogues in which His and pGlu residues were modified or replaced. The analogues were evaluated as agonists at TRH-R1 and TRH-R2 in cells in vitro, and in vivo in mice for analeptic and anticonvulsant activities. Several analogues bound to TRH-R1 and TRH-R2 with good to moderate affinities, and are full agonists at both receptor subtypes. Specifically, analogue 21 a (R = CH3) exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…This is consistent with our prior study using TRH receptor knockout mice, which showed that other effects of TAL, which are also most likely mediated by receptors in the central nervous system, require the TRH 1 , but not TRH 2 , receptor [11]. Although studies have examined the effects of TRH analogs with greater or lesser in vitro potencies for the TRH 1 or TRH 2 receptor [36, 37], to our knowledge, the current study and Thirunarayanan et al [11] are the only to employ TRH receptor knockout mice to determine which TRH receptor mediates a given response to TRH. Thus, we conclude that the TRH 1 receptor is the primary mediator of the anti-fatigue effects of TRH receptor agonists.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with our prior study using TRH receptor knockout mice, which showed that other effects of TAL, which are also most likely mediated by receptors in the central nervous system, require the TRH 1 , but not TRH 2 , receptor [11]. Although studies have examined the effects of TRH analogs with greater or lesser in vitro potencies for the TRH 1 or TRH 2 receptor [36, 37], to our knowledge, the current study and Thirunarayanan et al [11] are the only to employ TRH receptor knockout mice to determine which TRH receptor mediates a given response to TRH. Thus, we conclude that the TRH 1 receptor is the primary mediator of the anti-fatigue effects of TRH receptor agonists.…”
Section: Discussionsupporting
confidence: 90%
“…Available TRH analogs have higher affinities for the TRHR, longer half-lives, etc. (Engel et al, 2006; Khomane et al, 2011; Monga et al, 2011). …”
Section: Thyrotropin-releasing Hormone (Trh)mentioning
confidence: 99%
“…The resulting mixture was stirred at 4 °C for 36 h. After the completion of reaction, the solvent was removed under reduced pressure, and the residue thus obtained was purified by flash column chromatography using a stationary phase of neutral alumina and a mobile phase of 6% MeOH in CH 2 Cl 2 to afford 4a–e . 33 …”
Section: Experimental Sectionsmentioning
confidence: 99%